Occupational Health and Safety and Organizational Commitment: Evidence from the Ghanaian Mining Industry - Kwesi Amponsah-Tawiah; Justice Mensah (Elsevier, 2016)
Background: This study seeks to examine the relationship and impact of occupational health and safety on employees' organizational commitment in Ghana's mining industry. The study explores occupational health and safety and the different dimensions of organizational commitment. Methods: A cross-sectional survey design was used for this study. The respondents were selected based on simple random sampling. Out of 400 questionnaires administered, 370 were returned (77.3% male and 22.7% female) and used for the study. Correlation and multiple regression analysis were used to determine the relationship and impact between the variables. Results: The findings of this study revealed positive and significant relationship between occupational health and safety management, and affective, normative, and continuance commitment. Additionally, the results revealed the significant impact of occupational health and safety on affective, normative, and continuance commitment. Conclusion: Management within the mining sector of Ghana must recognize the fact that workers who feel healthy and safe in the performance of their duties, develop emotional attachment and have a sense of obligation to their organization and are most likely committed to the organization. Employees do not just become committed to the organization; rather, they expect management to first think about their health and safety needs by instituting good and sound policy measures. Thus, management should invest in the protection of employees' health and safety in organizations.